PENGARUH PENGAWASAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT KAMADJAJA LOGISTICS PEKANBARU - Hafizd Arafano Wianda; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims at the influence of work supervision and work motivation on the performance of employees of PT Kamadjaja Logistics Pekanbaru. Work supervision variable as a variable (X1), work motivation as a variable (X2) and performance as a variable (Y). This research method is descriptive quantitative using the SPSS 22 program, where the sample used is 62 employees using accidental sampling techniques and data collection techniques using a questionnaire. From the results of the data analysis which includes validity test, reliability test, determination test, simple linear regression test and multiple linear regression test, t test, f test so that it can be concluded that partially work supervision has a positive and significant effect on employee performance, partially working motivation. positive and significant effect on employee performance, work supervision and employee motivation simultaneously have a significant effect on employee performance at PT Kamadjaja Logistics Pekanbaru. Keywords: Motivation, organizational learning, organizational commitment